Studi Analisis Perilaku Jembatan Pejalan Kaki Dengan Sambungan Sekrup Dan Adhesive Pada Cold-Formed Steel - Indarto, Richo Oktavian; Suswanto, Budi (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2020)
Pedestrian Bridge is currently built in the city center of Indonesia. Generally, Pedestrian Bridge was built for connecting one to the other building and serve crossing bridge for the traffic. Therefore, design of Â the bridge must be considered of the function. Steel frame bridge (Hot Rolled) is one of the type bridge materials that used in Indonesia because the structure, the availability materials and the easy installation. Â Mild steel frame structure is one of the materials which used in the construction of Â pedestrian bridge. Its connected with plates, screws or adhesive.This research analyzed mild steel frame structure connected with screws and adhesive. Modeling of the pedestrian bridge used 4800 x 750 x 1200 mm. Comparation of the analysis used auxiliary program ABAQUS and SAP2000. The result of the analysis by ABAQUS is able to hold the force into 1003,69 kg and 1312,96 kg.